Multinational Military Cooperation in the Global South - Wachholtz, Matias Ferreyra; Soeters, Joseph (Sage Publications Inc, 2022)
In the 21st century, three international military organizations with standing headquarters in the Global South have emerged in the field of military operations. These are the Southern Cross Peace Force in Latin America, the Africa Standby Force, integrating five subregional African forces, and the Peninsula Shield Force in the command structures of the Gulf Cooperation Council countries. This article examines interorganizational differences and similarities in these three important cases, aiming to provide a deeper understanding of their organizational forms within the global diffusion phenomenon of multinational military cooperation. The article uses a novel comparative framework that bridges a gap in systematic studies of multinational military organizations. It aims to provide a gateway for theoretical growth now and for future studies, in the Global South and elsewhere.
Keywords: Multinational military cooperation; Global South; Diffusion; Isomorphism; Dependence; Comparison